A New Muscarine-Containing Inosperma (Inocybaceae, Agaricales) Species Discovered From One Poisoning Incident Occurring in Tropical China - Deng, Lun-Sha; Yu, Wen-Jie; Zeng, Nian-Kai; Zhang, Yi-Zhe; Wu, Xiao-Peng; Li, Hai-Jiao; Xu, Fei; Fan, Yu-Guang (Frontiers in Microbiology, 2022)
Currently, mushroom poisoning still poses a huge problem to humans’ health and life globally. Poisoning incidents caused by Inosperma spp. were reported continuously in tropical China in recent years. In this study, a new poisonous Inosperma species, discovered from a poisoning incident, was described from tropical China based on morphological, molecular, and toxin detection evidences; detailed descriptions, photographs, and comparisons to closely related species were provided. For qualitative analysis, through targeted screening using ultra-high liquid chromatography triple quadrupole mass spectrometry (UPLC-MS/MS), the new species contains muscarine, and no other toxins (two isoxazole derivatives, two tryptamine alkaloids, three amatoxins, and three phallotoxins). For quantitative analysis, muscarine contents in the pileus and stipe were 2.08±0.05 g/kg and 6.53±1.88 g/kg, respectively.